If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.28x + 602 = 0 Reorder the terms: 602 + -0.28x = 0 Solving 602 + -0.28x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-602' to each side of the equation. 602 + -602 + -0.28x = 0 + -602 Combine like terms: 602 + -602 = 0 0 + -0.28x = 0 + -602 -0.28x = 0 + -602 Combine like terms: 0 + -602 = -602 -0.28x = -602 Divide each side by '-0.28'. x = 2150 Simplifying x = 2150
| 3d^2-17d+20= | | 6t^2+25t+11= | | 11w^2-14w+3= | | 15x^2+58x+48=0 | | 7d^2+50d+7= | | 2n^2+15n+7= | | 6+4n-2=0 | | y=17x+85 | | 5x^2+24x=-15 | | x^6-52x+51=0 | | 12=y-36 | | -12y=-36 | | x-.25=31.6 | | q+(-1)=15 | | -7-4=-11 | | -75n=n+9 | | 6x+23=16x-71 | | (x^2)=1.8(0.3-x) | | 6-15(x+2)+12x=6x-(3x-4)+20 | | 2(3x-2)=4(x+2) | | 45+0.12x=49.32 | | (B+2)(-B^2+4b-3)= | | 8-6(x+4)+4x=4x-(2x-5)+11 | | 4x(3x+2)-3x(4x-5)=3x-8 | | (2z+9)(z-7)= | | (-x^4)+(8x^2)-2=0 | | (4w-4)(5w+6)= | | 7x=12x+10 | | X+8+x-6=3(x-5) | | 13d-5=60 | | -8p-8=56 | | (-2a-9)+(9+4)= |